LAWS: Language Annotation Web System Using ELAN Format - Estumano, Jeremias Kalebe; Nogueira, Antônia Fernanda de Souza; Amaris, Marcos (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2025: Anais do XXI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2025.246486, 2025)
Context: Linguists dedicate extensive time to annotating audiovisual media, where the efficiency of annotation tools significantly impacts their productivity. Existing tools, such as ELAN, are wellknown and widely used but present challenges due to their complex interfaces, especially for novice users. Solution: To overcome these challenges, we propose LAWS, a web-based linguistic annotation tool that emphasizes simplicity, intuitiveness, and a user-friendly interface to improve accessibility and usability for linguists. Methodology: The development of LAWS focused on streamlining access, handling, and documentation processes in linguistic annotation through a visually accessible web-based platform designed to reduce learning curves and enhance user experience. Results: LAWS offers a straightforward alternative to traditional tools, addressing usability gaps and providing linguists with an efficient, easy-to-navigate solution for their annotation tasks. Conclusions: By simplifying the linguistic annotation process, LAWS empowers linguists with an intuitive tool, promoting productivity and reducing the barriers associated with complex annotation software.